Role of Neutrophils in Psoriasis - Wen-Ming Wang; Hong-Zhong Jin (Journal of Immunology Research)
Psoriasis is a common inflammatory disease that can involve the skin, joints, or both. The abnormalities of innate immunity play crucial roles in the pathogenesis of psoriasis. Neutrophils are the most abundant leukocytes in the circulation. Emerging evidences have demonstrated that neutrophils may play a role in autoimmune diseases. The neutrophil-to-lymphocyte ratio (NLR), the activity of neutrophils, and the number of NETotic cells were significantly higher in psoriasis patients compared to healthy controls. The number of low-density granulocytes (LDGs) in the blood of psoriasis patients was significantly higher than those in the control blood. Furthermore, neutrophils may play important roles in the cardiovascular risk in psoriasis. However, the exact role of neutrophils in psoriasis remains unclear. In this review, we highlight the role of neutrophils in the pathogenesis of psoriasis.